Association between Handgrip Strength and Oral Hygiene Skills Among The Older People in Rural Area: A Pilot Study - Sari, Kartika Indah; Rizki, Friska Nur; Komara, Ira; Ong, Paulus Anam; Purba, Ambrosius; Widyaputra, Sunardhi (Journal of Indonesian Dental Association, 2021)
Introduction: The aging process is characterized by a decrease in muscle mass and muscle strength. It causes the deterioration of handgrip muscles. Diminishing handgrip strength can impact the activities of daily life, including the maintenance of oral hygiene. A toothbrush handle must be gripped firmly enough to remove plaque. Objectives: The aim of this study was to examine handgrip muscle strength and oral hygiene skills in the elderly. Methods: This study was a correlational analysis using a cross-sectional study design with a consecutive sampling technique of the elderly. The study was conducted in the rural village of Sinartanjung, Banjar, West Java, Indonesia. Handgrip strength was measured twice using an Electronic Hand Dynamometer Camry EH 101. Oral hygiene skills were assessed using the O'Leary plaque index to measure plaque control. Data were presented in tables and as percentages. A non-parametric statistical Spearman rank test was used to measure the correlation between handgrip strength and oral hygiene skill. Results: Forty-two the elderly people participated in this study, 31 females (73.80%) and 11 males (26.19%). The average handgrip strength was in the normal category (19.80 ± 7.2) kg and the average plaque index was in the moderate category (0.34 ± 0.16). The Spearman rank correlation test showed a significant correlation between handgrip strength and oral hygiene skills, r=0.521, p=0.000 (p <0.05). Conclusion: Maintained handgrip strength in the elderly ensures an adequate toothbrush grip, thereby improving oral hygiene skills and increasing the amount of plaque that can be removed.